Sensor for monitoring corrosion under various environments - Tan, Yong Jun. (2008)
A novel electrochemical corrosion sensor technology has been developed based on an electrochemically integrated multi-electrode array namely the wire beam electrode (WBE), in conjunction with electrochemical noise analysis (ENA). Scientifically, this WBE-ENA technology has overcome some major limitations associated with existing corrosion monitoring techniques in measuring localized corrosion. Technologically, a new instrument has been developed together with corrosion sensors for the detection and prediction of pre-mature failure of metallic structures in various environments. This new technology has been tested under various laboratory and practical corrosion and inhibition environments.